Edukasi Tentang Manajemen Laktasi dan Nutrisi Bayi sebagai Upaya Pencegahan Stunting oleh Kader - Fairuz Prihatin Idris; Andi Asrina; ST. Nurul Izzah Habibarrahman; Munifah Yusriah A.; Muh. Alif Reski; Andi Dindha Batari R. (Universitas Pahlawan Tuanku Tambusai, 2022)
Breast milk is the perfect and best food for babies, especially babies 0-6 months. In fact, the movement to exclusively breastfeed is considered to be lacking in echo and lack of support from many parties, including support from health workers. Purpose: Emprovide Education on lactation management, infant nutrition, and skills. Method: educational method with the concept of lectures and mentoring skills on Breastfeeding KIT and flipchart media. Results: there was an increase in knowledge as evidenced by the value (Z=-4.942; and p value=0.000 (p0.05). Evaluation: the form of measurement of the results of the pre and post test questionnaires that prove an increase in knowledge and attitudes as well as changes in attitude. Outputs: an increase in knowledge and skills as well as a change in attitude and the publication of mass media and scientific journals.